Relationship between Motives of Constructing Ethnic Identity and Individual Values among Russian High Schoolers from the Central and Far Eastern Regions of Russia - N.V. Murashcenkova; V.V. Gritsenko; E.V. Kulesh (Социальная психология и общество)
Objective. The aim of the study is to verification the hypothesis about the regional specificity of the relationship between the motives of constructing ethnic identity and individual values among Russian high schoolers from the central and far eastern regions of Russia. Background. Youth are a particularly vulnerable group in situations of permanent uncertainty and atypical crises. It is therefore important to explore the resource potential of different types of social identity and its factors among young people. Study design. We have conducted a comparative quantitative analysis of the results of the survey of the ethnic majority from the two mono-ethnic Russian regions (in May 2023). Participants. Russian high schoolers ages 15 to 18 from Smolensk (185 Russians, M = 16,3, SD = 0,48, 59,5% of girls) and Khabarovsk (134 Russians, M = 16,8, SD = 0,72, 67,9% of girls) participated in the study. Measurements. We used the Scale of Rapid Assessment of Ethnic Identity by N.M. Lebedeva, “Portrait Values Questionnaire” by S.H. Schwarz and author’s items formulated to assess motives of constructing ethnic identity. Results. Most respondents clearly feel themselves to be members of the Russian ethnic group, but do not see ethnic identity as a significant resource for meeting important needs. The dominant value basis of ethnic identity motives for Russian high schoolers from Smolensk is the Tradition value, and for Russian high schoolers from Khabarovsk – the Achievement value and the Universalism-Nature value. Conclusions. There is a regional specificity of formation and value bases of construction of the Russian ethnic identity among young members of the ethnic majority in conditions in mono-ethnic environment.